DINAMIKA USHULUL FIQH SEBAGAI DISIPLIN ILMU (STUDI KOMPARATIF PEMIKIRAN IMAM AL-GHAZALI DAN IMAM SYATHIBI DALAM QAT>’I> DAN Z>>ANNI>) - Muhammad Yusuf Yahya (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2023)
The research aims to describe the development of Usul Al-Fiqh as one of disciplinary knowledge by inquiry of Ghazali’s thought that is recognised as those who are influenced by Syafi’i’s school of law and it is briefly compared to Imam Syathibi’s (p. 1388) manner of thought as well as his method of Islamic law formulation. He is recognised as one who firmly adheres and becomes a loyal disciple of Maliki’s school of law even though when we in-depth inquiry the map of his thought, we should find he is frequently influenced by Imam Hanafi’s thought too. The research uses the qualitative approach which elucidates and analyzes the results of research. The collection technique of data is literature study. The research concludes that is according to Imam Ghazali, the scope of zanni (uncertainty) could be justified by qat‘i (certainty in context). Otherwise, the scope of qat‘i (certainty in context) might not be justified by zanni (uncertainty in context). The scope of qat‘i (certainty) that has been accompanied by qat‘i indicators (including the Qur’an verses and Hadis) could not hide the evident meanings even though it leads to ihtimalat (applicative meanings), which probably turns to various meanings. Thereby, Imam Ghazali’s thought assumedly denies qat‘i indicators used as reference to understand qiyas (legal analogy) towards the case that solely leads to one affirmation of jurisprudence product